Mina’s Self-Determination Expressed in Axie Oh’s The Girl Who Fell Beneath the Sea - Nafi’ah, Ufi; Andayani, Ambar (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
Abstract. This study explores the expression of self-determination in the character Mina from Axie Oh’s The Girl Who Fell Beneath the Sea, using the framework of Self Determination Theory (SDT) by Edward L. Deci and Richard M. Ryan (2000). The research applies a literary psychology approach and uses qualitative descriptive methods to analyse Mina’s intrinsic and extrinsic motivations throughout the novel. The findings reveal that Mina fulfills the three core needs of SDT: autonomy, competence, and relatedness. Her decision to sacrifice herself is rooted in personal values rather than external rewards, demonstrating strong intrinsic motivation. Additionally, her character development reflects a progression through various forms of extrinsic motivation, from external regulation to integrated regulation, showing how external pressures are gradually internalized. The study concludes that Mina’s psychological growth and self-determined actions offer a clear literary representation of SDT principles, contributing to a deeper understanding of motivation and identity in fictional narratives. Keywords: Extrinsic Motivation, Intrinsic Motivation, Self-determination.